The Silent Crises: The Future of Population in East Asia’s Leading Economies - Frisca Alexandra (Hasanuddin University, 2026)
Declining fertility has become one of the most significant demographic challenges facing advanced economies in East Asia. This article examines the dynamics of declining birth rates in China, Japan, and South Korea and their implications for long-term economic sustainability and social stability from a Non-Traditional Security perspective. This study employs a comparative qualitative approach using secondary data derived from international reports, national statistics, and relevant academic literature. The findings suggest that declining fertility in these countries is driven by a combination of economic pressures, shifting social values, and the limited effectiveness of pro-natalist policies. In the long term, persistent low fertility is likely to accelerate population ageing, reduce the size of the labour force, and increase pressure on welfare systems. Therefore, the fertility crisis in East Asia should be understood as a multidimensional challenge that requires comprehensive and long-term policy responses.